Bacillus Calmette–Guérin vaccine, antimalarial, age and gender relation to COVID-19 spread and mortality. Issue 35 (31st July 2020) - Osama El-Gendy, Ahmed; Saeed, Haitham; Ali, Ahmed M.A.; Zawbaa, Hossam M.; Gomaa, Dina; Harb, Hadeer S.; Madney, Yasmin M.; Osama, Hasnaa; Abdelrahman, Mona A.; Abdelrahim, Mohamed E.A.
Highlights: COVID-19 is affecting different countries all over the world with great variation in infection rate and death ratio. Some reports suggested a relation between the Bacillus Calmette-Guérin (BCG) vaccine and the malaria treatment to the infection prevention. Some reports related infant's lower-susceptibility to the BCG vaccine. Some other reports a higher risk in males compared to females in such a COVI-19 pandemic. Some other reports claimed the possible use of chloroquine and hydroxychloroquine as prophylactic in such a pandemic. The-present commentary is to discuss the possible relation between those-factors and SARS-CoV-2 infection. Abstract: COVID-19 is affecting different countries all over the world with great variation in infection rate and death ratio. Some reports suggested a relation between the Bacillus Calmette-Guérin (BCG) vaccine and the malaria treatment to the prevention of SARS-CoV-2 infection. Some reports related infant's lower susceptibility to the COVID-19. Some other reports a higher risk in males compared to females in such COVID-19 pandemic. Also, some other reports claimed the possible use of chloroquine and hydroxychloroquine as prophylactic in such a pandemic. The present commentary is to discuss the possible relation between those factors and SARS-CoV-2 infection.